Respon Pertumbuhan Tanaman Reklamasi PT Newmont Nusa Tenggara terhadap Penggunaan Mulsa Organik Kardus - Iwan Hilwan; Meida Rosani (Jurnal Silvikultur Tropika, 2020)
Plant growth determined factors such as environmental manipulation of seeds, including maintenance and pest disease prevention integrated. Intensive maintenance needs to be done especially when the plant is still young-old. Use organic mulch cardboard including part of plant maintenance to suppress weed competition with staple crops at a young age. In addition the use of mulch, organic boxes are expected to give positive influence against the growth of staple crops and chemical properties as well as land reclamation in soil biology. The results showed that organic mulching cardboard gives positive influence against the reclamation plant growth based on parameters of high and in diameter. The development of plants under around staple crops can be suppressed. Chemical properties of the soil showed improvement in some elements of the chemistry of the soil with organic mulch using cardboard. The diversity of types of makrofauna the soil around the plants with mulch treatments staple cardboard categories include being with Shannon's Diversity index value-Wiener of 1.57 while in treatment control categories include low value of 1.48. Keywords: cardboard mulch, plant growth, reclamation, weed